Motivation to learn in online environments : an exploration of two tertiary education contexts : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Education at Massey University, Manawatu, New Zealand - Hartnett, Margaret Katherine (Massey University, 2010)
Research evidence suggests that motivation is an important consideration for online learners. Notably, existing research has frequently focused on the design of motivating online learning environments. Alternatively, motivation has been viewed as a collection of relatively stable personal characteristics of learners. In contrast, a contemporary view that acknowledges the complexity and dynamic interplay of factors underlying and influencing motivation to learn (e.g., Turner & Patrick, 2008) is adopted here. From this „person in context‟ perspective, this study investigates the nature of motivation to learn in online distance learning environments. The study explores how student motivation relates to online participation in these contexts. In addition, social and contextual factors that foster and undermine motivation are identified. The research design utilises a case study approach which focuses on learners in two separate online distance courses within the same university programme. The boundary for each case study is defined by one piece of assessed work and the associated activities within each course. Interview and questionnaire data, supported by archived online data and course resources, were collected. Analysis of the data were made using the three conceptual lenses of self-determination theory (Deci & Ryan, 1985) and the continuum of human motivation encompassed within this theoretical framework. Findings indicate that the motivation of learners in online environments was multidimensional. Intrinsic motivation and various types of extrinsic motivation were shown to co-exist. Complex relationships were also shown to exist between motivation and participation that were sensitive to situational influences. Multiple factors fostered the expression of high quality (i.e. more self-determined) motivation. Most prominent among these were the relevance of the learning activity, the provision of clear guidelines, and ongoing support and feedback from the teacher that was responsive to learners‟ needs. Supportive caring relationships were also important. A range of factors also undermined the motivation of learners; most notably high workload, assessment pressure, and the perception that the learning activity lacked relevance.
Keywords: Online learning; Tertiary education; Higher education; Motivation; Fields of Research::330000 Education::330100 Education Studies::330107 Educational technology and media